Neurocognitive impact of different irradiation modalities for patients with grade I-II skull base meningioma: a prospective multi-arm cohort study (CANCER COG) - Paul Lesueur; Florence Joly; Benedicte Clarisse; Justine Lequesne; Dinu Stefan; Jacques Balosso; Marie Lange; Sebastien Thureau; Aurelie Capel; Marie Castera; Berenice Legrand; Nicolas Goliot; et al. (Radiation Oncology)
Abstract Background Radiotherapy as a complement or an alternative to neurosurgery has a central role in the treatment of skull base grade I-II meningiomas. Radiotherapy techniques have improved considerably over the last two decades, becoming more effective and sparing more and more the healthy tissue surrounding the tumour. Currently, hypo-fractionated stereotactic radiotherapy (SRT) for small tumours and normo-fractionated intensity-modulated radiotherapy (IMRT) or proton-therapy (PT) for larger tumours are the most widely used techniques. It is expected a decrease of the risk of cognitive impairment with these modern techniques. However prospective data about cognitive long-term consequences of partial brain irradiation with SRT, PT, or IMRT remain very scarce to date. Methods CANCER COG is one of the first multicentric study in the world to prospectively assess the cognitive performances of patients following different modalities of cerebral radiotherapy (stereotactic radiotherapy, proton therapy, intensity modulated radiotherapy) for the treatment of grade I-II skull base meningioma, up to at least 10 years after the end of radiotherapy. This longitudinal study includes the follow-up of 3 cohorts, including: patients treated with PRT, IMRT, and SRT. An additionally control group will be formed. The primary objective is to report long-term cognitive deterioration in each cohort until 10 years after the end of irradiation. The rate of clinical symptomatology improvement over time after irradiation, the evolution of health-related quality-of-life, anxiety/depression, fatigue, over time after irradiation, the tumoral local control after irradiation, the progression-free survival (PFS), the professional reintegration for working-age patients will also be assessed. CANCER COG aims to help clinicians to choose the best irradiation techniques with the best benefit/risk ratio. Inclusions started on september 2023. Trial registration The study was registered on clinicaltrials.gov with the following number: NCT 06036706.